Development of on-line information system for Lestari Tuition Centre / Siti Nur Baizura Mokhtar - Mokhtar, Siti Nur Baizura (2006)
This project is an online student information system for Lestari Tuition Centre that can be accessed by students, parents and administrator through internet. The system provides services and information for students such as general and personal information, timetable and the result of examination. It also can be used by administrator to update information of students. The system provides convenient way for all students to search information, like the information about Lestari Tuition Centre. The system also enables students to view their examination result online. The parents of the students also can view the result and timetable of their children. Besides that, this information system also provides with the fees information for each student that has been registered at this institution. On the other hand, the administrator can perform the basic database queries such as, work with the system to update, delete, view, add the student's, teacher's and parent's information. The technologies used in the project are ASP Java Script and ASP VB Script, Microsoft Dream weaver MX 2004. The database is created using Microsoft Access and web server is run on Window XP Professional with Internet Explorer.